2018
DOI: 10.1111/dom.13194
|View full text |Cite
|
Sign up to set email alerts
|

Ertugliflozin plus sitagliptin versus either individual agent over 52 weeks in patients with type 2 diabetes mellitus inadequately controlled with metformin: The VERTIS FACTORIAL randomized trial

Abstract: AimTo evaluate the efficacy and safety of ertugliflozin and sitagliptin co‐administration vs the individual agents in patients with type 2 diabetes who are inadequately controlled with metformin.MethodsIn this study (http://Clinicaltrials.gov NCT02099110), patients with glycated haemoglobin (HbA1c) ≥7.5% and ≤11.0% (≥58 and ≤97 mmol/mol) with metformin ≥1500 mg/d (n = 1233) were randomized to ertugliflozin 5 (E5) or 15 (E15) mg/d, sitagliptin 100 mg/d (S100) or to co‐administration of E5/S100 or E15/S100. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
182
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 133 publications
(208 citation statements)
references
References 26 publications
20
182
1
5
Order By: Relevance
“…5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes. 5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes. 5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes. 5 Similar to these results, on a background of metformin, ertugliflozin at 5-and 15-mg doses provided sustained glycemic control over 52 weeks. 5,7,22,23 Coadministration of ertugliflozin with sitagliptin 100 mg provided greater glycemic control compared with each individual dose of ertugliflozin and sitagliptin with inadequate control on either metformin or diet and exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of phase 3 studies of ertugliflozin in patients with T2DM inadequately controlled with diet and exercise alone demonstrate that, when used either as monotherapy or in combination with sitagliptin, at doses of 5 mg and 15 mg for 26 weeks, ertugliflozin provided effective glycemic control, reduced body weight, and was generally well tolerated. Other phase 3 studies have shown that administration of ertugliflozin at doses of 5 mg or 15 mg to patients with T2DM inadequately controlled on metformin or metformin and sitagliptin provided more effective glycemic control over 26 weeks compared with placebo or that, when coadministered with sitagliptin, provided more effective glycemic control compared with either agent alone …”
mentioning
confidence: 99%
“…Each study underscored the SGLT‐2 inhibitor's efficacy. In the VERTIS FACTORIAL study, 1233 patients with type 2 diabetes (T2D) on stable metformin therapy were randomized to one of five arms: 5 mg ertugliflozin, 15 mg ertugliflozin, 100 mg sitagliptin (a dipeptidyl peptidase‐4 [DPP‐4] inhibitor branded as Januvia by Merck), a combination regimen of 5 mg ertugliflozin and 100 mg sitagliptin, or a combination regimen of 15 mg ertugliflozin and 100 mg sitagliptin. After 52 weeks, HbA1c declined by 1.4% from a baseline of 8.6% in both combination therapy groups compared with an HbA1c decline of approximately 1% from the same baseline in all monotherapy groups.…”
mentioning
confidence: 99%